REVIEW ARTIKEL: PEMANFAATAN SELONGSONG MAGGOT (Hermetia illucens) SEBAGAI SUMBER KITIN DAN BAHAN DASAR KITOSAN - Reza Setiawan; Daniel Daniel (PROSIDING SEMINAR KIMIA, 2023)
Cultivation of black soldier fly (Hermetia illucens) is mushrooming in Indonesia recently because of its benefits, including the BSF larvae is rich in protein and helps reduce waste pollution. One of the byproducts of this cultivation is the pupal exuviae which is still not utilized properly. Pupal exuviae of black soldier fly contain chitin and can be processed into chitosan. The purpose of this article is to review the results of research on the synthesis of chitosan based on pupal exuviae of black soldier fly from various articles. The method used in this research is the literature review method. The results of the literature review showed that pupal exuviae of black soldier fly content of around 12-30% due to the extraction method used. The structure of chitin and chitosan were characterized by FTIR, XRD, and SEM. The characterization results showed that the physical characteristics of BSF chitin were α-chitin. The crystal index values of chitin is 52.8%, while chitosan is 55.4%. The surface morphology of chitin and chitosan is nanofiber structures. Based on the overall reviews, it can be concluded that pupal exuviae BSF can be an alternative source of chitin and processed into chitosan which is useful for various technological purposes. Keywords: Hermetia illucens, chitin, chitosan, pupal exuviae BSF